Characterization of soil moisture dynamics in Colombian agricultural areas - Hernández-Guzmán, Francisco Javier; Cleves-Leguizamo, José-Alejandro; Díaz-Almanza, Eliecer David (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
Seasonal dynamics in edaphic humidity are influenced by different environmental factors, such as topography, physical and chemical soil conditions, type of vegetation cover and climatic classification. Data from 105 agrometeorological stations in the IDEAM network, distributed throughout Colombia, with records from January, 2001 to April, 2020, were studied. A non-parametric Spearman rank correlation test was used to evaluate the relationship between soil moisture and atmospheric variables. Simultaneously, the behaviors of seasonal dynamics were analyzed, along with their interaction with atmospheric, physical soil and vegetation cover variables. The results showed that soil moisture is more significantly influenced by frequency than by intensity of precipitation; this variable had a seasonal behavior, similar to that of precipitation. The physical variable texture was closely related to the behavior of the soil surface moisture (<10 cm deep). In addition, there was evidence of a surface moisture response to the physical conditions of the soil, topography and availability of plant cover. As the soil depth increased, the soil moisture had less variation because the influence of the atmospheric conditions was greater on the surface and persisted longer over time.